Object Oriented and Rule-based Design of Visual Languages using Tiger - Ermel, Claudia; Ehrig, Karsten; Taentzer, Gabriele; Weiss, Eduard (Electronic Communications of the EASST, 2007)
In this paper we present the state-of-the-art of the TIGER environment for the generation of visual editor plug-ins in Eclipse, with the focus on its Designer component, a visual environment for object oriented and rule-based design of visual languages. Based on an alphabet for finite automata we show how a visual language can be designed by defining the abstract and concrete syntax of the visual language and syntax directed editing operations in the generated editor plug-in. For the graphical layout we use the Graphical Editing Framework (GEF) of ECLIPSE which offers an efficient and standardized way for graphical layouting.